Profit shifting by multinational corporations in Kenya: The role of internal debt - Roseline Nyakerario Misati; Kethi Ngoka; Anne Kamau; Maureen Odongo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Illicit financial flows directly impact a country's ability to raise, retain, and mobilize its own resources to finance sustainable development. Against a backdrop of a weak public financial position attributed to capital flight, tax avoidance, and dependence on corporate income taxes, governments in Africa face impediments to their efforts to widen the tax base. Using firm-level annual data from 2015-19 from multinational corporations' audited financial statements, we assess the scale of profit shifting by those corporations with a presence in Kenya. Using a panel analysis, the study delves into the incentives for profit shifting, focusing on internal debt. It finds that a 10 per cent increase in the difference between Kenya's corporate tax rate and that of the lending corporation's home country increases the internal debt ratio by between 1 and 2 per cent. The results provide a basis for the design of targeted tax and revenue administration reforms against the backdrop of rising revenue needs.
Keywords: F23; H25; H26; O23; 330; profit shifting; corporate tax rate; multinational corporations